Protocolo de elaboración de prótesis total revisión sistemática - Saca Reinoso, Evelyn Janeth (2025)
Background: the conventional technique in the elaboration of total prostheses, used for decades, is based on manual processes of taking impressions, making models and fabricating prostheses with acrylic re sins and wax. Despite the technological evolution in dentistry, the conventional methodology continues to be a standard in the restoration of function and esthetics in edentulous patients. Introduction: the elaboration of total prosthesis in dentistry i s c rucial to restore masticatory function and esthetics in edentulous patients. The conventional technique, used for decades, involves taking accurate impressions, constructing working models and fabricating the prosthesis with acrylic resins and wax. Obje cti ve: to determine the best protocol for the elaboration of conventional total prosthesis in systemic revision. Materials and Methods: a mixed methodology with a qualitative quantitative approach was used, reviewing bibliography in databases such as PubMe d, Google Scholar, Scielo and Elsevier. Relevant studies published between 2019 to 2024 were selected, identifying best practices and the most significant advances to improve conventional prosthetic care. Results: 60 articles and books were reviewed in the da tabase, of which 20 were excluded because they did not meet the inclusion criteria or were not related to the topic. Forty articles were analyzed, gathering key information for the elaboration of the total prosthesis protocol. Conclusion: the convention al technique for the elaboration of total prosthesis continues to be effective and valuable, offering consistent solutions for the restoration of function and esthetics in edentulous patients.